2019
DOI: 10.1049/iet-nbt.2019.0261
|View full text |Cite
|
Sign up to set email alerts
|

Wing‐kinematics measurement and flight modelling of the bamboo weevilC. buqueti

Abstract: Insects are one of the most agile flyers in nature, and studying the kinematics of their wings can provide important data for the design of insect-like wing-flapping micro aerial vehicles. This study integrates high-speed photogrammetry and three-dimensional (3D) force measurement system to explore the kinematics of Cyrtotrachelus buqueti during the wing-flapping flight. The tracking point at the wing tip of the hind wing was recorded using high-speed videography. The lift-thrust force characteristic of wing-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…It is positive when the position of the hindwing is on the ventral side. The angle between the average chord b 1 and the horizontal axis s 2 of the wind is defined as the angle of attack α(t) [20]. When the position of the leading edge of the hindwing is above the horizontal plane, the angle of attack is positive.…”
Section: Defining Appropriate Coordinate Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is positive when the position of the hindwing is on the ventral side. The angle between the average chord b 1 and the horizontal axis s 2 of the wind is defined as the angle of attack α(t) [20]. When the position of the leading edge of the hindwing is above the horizontal plane, the angle of attack is positive.…”
Section: Defining Appropriate Coordinate Systemsmentioning
confidence: 99%
“…It has also been found in dragonflies that the flapping trajectory affects the aerodynamics [19], providing inspiration for flapping trajectory variation in the design of MAVs. The flapping trajectories of the beetle C. buqueti have been used for kinematic modeling, which has yielded benefits when studying the aerodynamic properties of FWMAVs [20]. In addition, insects sometimes appear to have more than one flapping trajectory mode, which can allow for variable aerodynamic properties [21].…”
Section: Introductionmentioning
confidence: 99%
“…Research also shows that bio-inspired insect robots undergo a stabilization technique called vibrational stabilization, with exceptionally high frequencies [ 180 ]. Without the need to use a thrust force, some insect species generate the flapping lift sufficient to retain their body weight [ 181 ]. Researchers found that the CG repercussion on longitudinal flight stability is a common characteristic of all tailless flapping insect species, with research restricted to the longitudinal direction [ 182 ].…”
Section: Improvement In Future Wing Architecture and Miniaturized Drone Designsmentioning
confidence: 99%
“…The small deflection under uniformly distributed load and bending moment shows that the hind wing of C. buqueti has excellent structural performance [25]. The flapping pattern of the double figure-eight trajectory creates the excellent flight manoeuverability of C. buqueti [26]. The folding mechanism, kinematic data and morphological parameters of the wing of C. buqueti are simulated to design the deployable mechanism, and its rigid-flexible coupling dynamic characteristics of folding and unfolding are analysed.…”
Section: Introductionmentioning
confidence: 99%